The Small Intestine Converts Dietary Fructose into Glucose and Organic Acids - Jang, Cholsoon; Hui, Sheng; Lu, Wenyun; Cowan, Alexis J.; Morscher, Raphael J.; Lee, Gina; Liu, Wei; Tesz, Gregory J.; Birnbaum, Morris J.; Rabinowitz, Joshua D. (Cell metabolism, 2018)
Excessive consumption of sweets is a risk factor for metabolic syndrome. A major chemical feature of sweets is fructose. Despite strong ties between fructose and disease, the metabolic fate of fructose in mammals remains incompletely understood. Here we use isotope tracing and mass spectrometry to track the fate of glucose and fructose carbons in vivo, finding that dietary fructose is cleared by the small intestine. Clearance requires the fructose-phosphorylating enzyme ketohexokinase. Low doses of fructose are ∼90% cleared by the intestine, with only trace fructose but extensive fructose-derived glucose, lactate, and glycerate found in the portal blood. High doses of fructose (≥1 g/kg) overwhelm intestinal fructose absorption and clearance, resulting in fructose reaching both the liver and colonic microbiota. Intestinal fructose clearance is augmented both by prior exposure to fructose and by feeding. We propose that the small intestine shields the liver from otherwise toxic fructose exposure. [Display omitted] •Isotope tracing reveals that the small intestine metabolizes most dietary fructose•High-dose fructose saturates intestinal fructose clearance capacity•Excess fructose spills over to the liver and colonic microbiota•Intestinal fructose clearance is enhanced by feeding While it is commonly believed that the liver is the main site of fructose metabolism, Jang et al. show that it is actually the small intestine that clears most dietary fructose, and this is enhanced by feeding. High fructose doses spill over to the liver and to the colonic microbiota.